2006
DOI: 10.1007/s10734-006-9045-1
|View full text |Cite
|
Sign up to set email alerts
|

Learning ability, socioeconomic status, and student placement for undergraduate studies in Israel

Abstract: Choice of institution and field of study for a bachelor's degree in Israel was found essentially meritocratic although influenced by socioeconomic status (SES) as well. As expected, students of higher ability attend universities and those of lower apply to academic colleges. However, among students of higher ability, those of higher SES opt for prestigious professions, such as medicine and law, or natural or social sciences, while those of lower SES choose economics and management, computer science, paramedica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 29 publications
1
18
0
Order By: Relevance
“…In particular, the results indicate that parental expectations, whether they pertain to their children's educational attainment, their children's future mathematics‐related career, or school academic emphasis, are more important than parental achievements (as measured by their educational attainment and occupational status). These results are consistent with those reported in some studies (Hauser et al ., ; Dar & Getz, ). For example, Dar and Getz's () study alluded to the importance of student expectations for a university education.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the results indicate that parental expectations, whether they pertain to their children's educational attainment, their children's future mathematics‐related career, or school academic emphasis, are more important than parental achievements (as measured by their educational attainment and occupational status). These results are consistent with those reported in some studies (Hauser et al ., ; Dar & Getz, ). For example, Dar and Getz's () study alluded to the importance of student expectations for a university education.…”
Section: Discussionmentioning
confidence: 99%
“…On top of that, there are studies which have reported that a bachelor's degree in engineering could open up wider career opportunities with better remuneration than a science degree (e.g. Dar & Getz, 2007). Students who are interested in a science-oriented career would probably opt for Engineering programmes as they are usually perceived to provide better career prospects.…”
Section: Discussionmentioning
confidence: 99%
“…The three top reasons for selecting a course include career opportunities, ability, and grade. Dar and Getz (2007) noted that academically less bright students tend to pursue education and social science degrees, while brighter students tend to pursue science till graduate level. Their sample consisted of 1,538 second-and third-year Bachelor's degree students.…”
Section: Literature Review On Higher Education Preferencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher education needs to relocate itself with directions for change in the enhancement of experience on campus socio-economic status by women faculty in academics (Sheridan, Brennan, Carnes, & Handelsman, 2006). With social class often known to be impacting academic engagement (Kelly, 2008); the socio economic status is known leave its essentiality on learning ability and subsequent placement of students in the undergraduate study (Dar & Getz, 2007). The parental influence on work and family plans of adolescents diversifies by ethnic backgrounds (De Valk, 2008) where internet use for academic purpose is also found to be low among students with low socio-economic status (Aerschot & Rodousakis, 2008) with frequency of its use also varying by socio-economic status (Koc & Tamer, 2011).…”
Section: Academic Adaptationmentioning
confidence: 99%